2021
DOI: 10.3389/fevo.2021.740362
|View full text |Cite|
|
Sign up to set email alerts
|

Geometric Complexity and the Information-Theoretic Comparison of Functional-Response Models

Abstract: The assessment of relative model performance using information criteria like AIC and BIC has become routine among functional-response studies, reflecting trends in the broader ecological literature. Such information criteria allow comparison across diverse models because they penalize each model's fit by its parametric complexity—in terms of their number of free parameters—which allows simpler models to outperform similarly fitting models of higher parametric complexity. However, criteria like AIC and BIC do n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…Monod was working with low concentrations of bacteria, while Contois experimented with high concentrations (Arditi and Ginzburg, 2012). Nevertheless, compared to AGC, HVH, and BDA trophic functions, universal GRD functions do not demonstrate far superior performance and flexibility in fitting the observed data (Tyutyunov et al, 2010;Prokopenko et al, 2017;Novak and Stouffer, 2021b). Accordingly, simpler models provide just as good approximations to reality.…”
Section: Underlying Mechanisms and Minimal Model Of Predator Interferencementioning
confidence: 99%
“…Monod was working with low concentrations of bacteria, while Contois experimented with high concentrations (Arditi and Ginzburg, 2012). Nevertheless, compared to AGC, HVH, and BDA trophic functions, universal GRD functions do not demonstrate far superior performance and flexibility in fitting the observed data (Tyutyunov et al, 2010;Prokopenko et al, 2017;Novak and Stouffer, 2021b). Accordingly, simpler models provide just as good approximations to reality.…”
Section: Underlying Mechanisms and Minimal Model Of Predator Interferencementioning
confidence: 99%
“…These were theoretical works, and there has been little subsequent experimental exploration of functional responses in two or more prey systems involving diet choice based on handling/processing time. As a result, major reviews of empirical works have concentrated on studies of functional responses in single resource systems: this includes Jeschke et al (2002Jeschke et al ( , 2004, DeLong (2021), and Novak and Stouffer (2021b). The last of these (DeLong, 2021) has a chapter (Chapter 5) on "multispecies functional responses" and one (Chapter 7) on "optimal foraging".…”
Section: Choice Between Two or More Prey/resourcesmentioning
confidence: 99%
“…Ginzburg and Damuth (2022) have recently argued for an expanded ratio dependence in which the denominator (predator abundance) can be raised to a positive power other than 1. Various reviews have shown significant differences between the results of empirical measurements of predator effects and the original ratio-dependent models (Skalski and Gilliam, 2001;Novak and Stouffer, 2021b). An early critique of ratio dependence pointed out that there were many causes of predator-dependence, virtually none of which led to ratio dependence (Abrams, 1994).…”
Section: Predator-dependent Single-prey Modelsmentioning
confidence: 99%
See 2 more Smart Citations